Minister Recognises Our Role, Say Bloggers - Sunday Star (2008)
Bloggers In Malaysia describe Information Minister Datuk Ahmad Shabery Cheek's willingness to meet them as a recognition of the role played by the cyber community in shaping public opinion in the country.